Sacred places, emerging spaces : religious pluralism in the post-Soviet Caucasus - Darieva, Tsypylma; Mühlfried, Florian; Tuite, Kevin (Space and place, 2018)
"Though long-associated with violence, the Caucasus is a region rich with religious conviviality. Based on fresh ethnographies in Georgia, Armenia, Azerbaijan, and the Russian Federation, Sacred places, emerging spaces discusses vanishing and emerging sacred places in the multi-ethnic and multi-religious post-Soviet Caucasus. In exploring the effects of de-secularization, growing institutional control over hybrid sacred sites, and attempts to review social boundaries between the religious and the secular, these essays give way to an emergent Caucasus viewed from the ground up: dynamic, continually remaking itself, within shifting and indefinite frontiers."--